Investigation of a phase leg consisting of CoolMOS Transistors and frewheeling SiC shottky diodes - Isaksson, Mats-Åke; Öhnell, Björn (My University, 2007)
In power electronics, MOSFET transistors are continuously being important due to their low switching losses at high frequencies. However, a regular power MOSFET suffers from a relatively low breakdown voltage. In the late 1990’s the super junction MOSFET transistor was launched. It combines the low on state losses of an IGBT and the low switching losses of a MOSFET. In this project CoolMOS transistors from Infineon Technologies has been used. These are based on the super junction topology. The purpose of this project was to design, build and evaluate a two quadrant step down DC/DC converter with CoolMOS transistors and silicon -carbide Schottky diodes as free wheeling diodes. Based on the results, conclusions will be made about the transistor topology’s suitability for a high power application, for instance in a hybrid vehicle. Because of the structure of the CoolMOS, a diode has been put in series to prevent the current to flow in the negative direction through the transistors during its off state. From the simulation and measurements, the basic function of the two quadrant step down converter circuit is verified. The main problem with the circuit is the stray inductance in the wires and the capacitance in the series diode and transistors. These phenomena result in transients of the current through the transistors and in the voltage across the transistors. To prevent the transients, tighter design to minimize the stray inductance and capacitance must be achieved. An alternative is to construct a snubber to minimize the transients. The features of the CoolMOS are suitable for high power application due to its low losses. In such an application the bridge should be built as a single chip for optimal design and usability.
Keywords: Elkraftteknik; Electric power engineering